Integration Of Artificial Intelligence In Learning Islamic Religious Education Based On Emotional Intelligence In Primary Schools - Dwi Priyanto; Annisa Nuraisyah Annas; Andi Fitriani Djollong; Khaerul Khaerul; Yasir Arafat (PT. Banjarese Pacific Indonesia, 2025)
This research aims to analyze the integration of artificial intelligence (AI) in Islamic Religious Education (PAI) learning based on emotional intelligence (EQ) in elementary schools in order to increase the effectiveness of adaptive and characterful learning. This study focuses on the use of AI to personalize teaching materials, strengthen spiritual values, and develop students' empathy and social skills through an EQ-based approach. The method used is literature study by analyzing various sources such as journals, books and articles related to AI, PAI and EQ-based learning. The research results show that AI integration can facilitate interactive and enjoyable learning, while the EQ approach strengthens students' internalization of religious and emotional values. However, its success depends on collaboration between technology, teachers and a curriculum oriented towards the holistic development of children.